Audiovisual Demonstration Methods on The Knowledge and Behavior of Cadres About Stimulation of Massage Therapy in Improving Nutrition Status in Children - Fazrin, Intan; Anggraeni, Suci; Saputro, Heri (STRADA : Jurnal Ilmiah Kesehatan, 2021)
This study uses a pre-experimental one group pre-post test design. The population in this study were all cadres of Posyandu under five in the working area of ​​the Pesantren II Public Health Center, Pakunden Village, Kediri City, which amounted to 47 people. The number of respondents as many as 38 people were selected randomly using simple random sampling. Data analysis used paired t test. The results of the study showed that the mean value of knowledge before was 6.37 and after 7.42. The mean value for behavior before is 19.24 and after 19.79, so it can be concluded that there is an increase in knowledge and behavior of cadres. There was an effect of giving the audiovisual demonstration method on the knowledge of cadres about massage therapy stimulation in improving nutritional status in children (Sig. 0.003 <0.05) and cadres' behavior about massage therapy stimulation (Sig. 0.004 <0.05)